2009
DOI: 10.1007/s00701-009-0552-6
|View full text |Cite
|
Sign up to set email alerts
|

Meningiomas in the elderly, the surgical benefit and a new scoring system

Abstract: The present results suggest that common experience-based considerations may be optimized and implemented into a simple scoring system that in turn may allow for outcome prediction and evidence-based decision making

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 10 publications
3
49
0
Order By: Relevance
“…Several studies have assessed predictors for surgical outcome in elderly meningioma patients using CRGS, GSS and SKALE scoring systems that include tumor size, gender, KPS score, ASA score, tumor location, peritumoral edema and concomitant disease (9,10,16). The CRGS, GSS and SKALE scoring systems have been proposed for use in patients aged over 70, 65 and 80 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have assessed predictors for surgical outcome in elderly meningioma patients using CRGS, GSS and SKALE scoring systems that include tumor size, gender, KPS score, ASA score, tumor location, peritumoral edema and concomitant disease (9,10,16). The CRGS, GSS and SKALE scoring systems have been proposed for use in patients aged over 70, 65 and 80 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that a poor outcome following surgical treatment for intracranial meningiomas in the elderly was associated with a score ≤9, ≤15 and ≤7 for the CRGS, GSS and SKALE, respectively (15)(16)(17). The cut-off point for postoperative complications was ≤9, ≤15, and ≤7 for CRGS, GSS, and SKALE, respectively (9,15,17). Multivariate logistic regression analysis revealed no significant associations between patient age (≥75 years), lower CRGS (≤9), GSS (≤15), and SKALE scores (≤7) and surgical complications (P= 0.0992, P= 0.7935, P= 0.1414 and P= 0.6441, respectively) (Table IV).…”
Section: ------------------------------------------------------------mentioning
confidence: 92%
See 2 more Smart Citations
“…After screening of the title and abstract, 1377 irrelevant studies were excluded. Then, three studies were excluded for irrelevant outcomes [26][27][28] (Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%